Intraocular lenses in children: changes in axial length, corneal curvature, and refraction. Issue 3 (1st March 1999) - Flitcroft, D I; Knight-Nanan, D; Bowell, R; Lanigan, B; O'Keefe, M
Abstract : AIM: To assess changes in axial length, corneal curvature, and refraction in paediatric pseudophakia. METHODS: 35 eyes of 24 patients with congenital or developmental lens opacities underwent extracapsular cataract extraction and posterior chamber intraocular lens implantation. Serial measurements were made of axial length, corneal curvature, objective refraction, and visual acuity. RESULTS: For patients with congenital cataracts (onset <1 year age) the mean age at surgery was 24 weeks. Over the mean follow up period of 2.7 years, the mean increase in axial length of 3.41 mm was not significantly different from the value of an expected mean growth of 3.44 mm (paired t test, p=0.97) after correction for gestational age. In the developmental cataract group (onset >1 year of age) the mean age at surgery was 6.4 years with a mean follow up of 2.86 years. This group showed a mean growth in axial length of 0.36 mm that was not significantly different from an expected value of 0.47 mm (paired t test, p = 0.63). The mean preoperative keratometry was 47.78 D in the congenital group and 44.35 D in the developmental group. At final follow up the mean keratometry in the congenital group was 46.15 D and in the developmental group it was 43.63 D. In eyes followed for at least 2 years, there was an observed myopic shift by 24 months postoperatively of 3.26 D in the congenital cases (n=10) and 0.96 D in the developmental cases (n=18). CONCLUSION: The pattern of axial elongation and corneal flattening was similar in the congenital and developmental groups to that observed in normal eyes. No significant retardation or acceleration of axial growth was found in the eyes implanted with IOLs compared with normal eyes. A myopic shift was seen particularly in eyes operated on at 4–8 weeks of age and it is recommended that these eyes are made 6 D hypermetropic initially with the residual refractive error being corrected with spectacles.